2018
DOI: 10.1371/journal.pone.0196986
|View full text |Cite
|
Sign up to set email alerts
|

Increased α-actinin-1 destabilizes E-cadherin-based adhesions and associates with poor prognosis in basal-like breast cancer

Abstract: The controlled formation and stabilization of E-cadherin-based adhesions is vital for epithelial integrity. This requires co-operation between the E-cadherin-based adhesions and the associated actin cytoskeleton. In cancer, this co-operation often fails, predisposing cells to migration through molecular mechanisms that have only been partially characterized. Here, we demonstrate that the actin filament cross-linker α-actinin-1 is frequently increased in human breast cancer. In mammary epithelial cells, the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 73 publications
1
47
0
Order By: Relevance
“…Additionally, membrane bound E-cadherin was lost indicating loss of cell-cell adhesion. To maintain a polarized epithelium, actin cytoskeleton co-operates with E-cadherin- and integrin-based cell-cell or cell-matrix adhesions[26]. α-actinin which is a major actin filament crosslinker was significantly upregulated in mild KC epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, membrane bound E-cadherin was lost indicating loss of cell-cell adhesion. To maintain a polarized epithelium, actin cytoskeleton co-operates with E-cadherin- and integrin-based cell-cell or cell-matrix adhesions[26]. α-actinin which is a major actin filament crosslinker was significantly upregulated in mild KC epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty out of 62 (48%) differentially expressed proteins between C1, C2, and C3 belonged to biological categories which characterized these TNBC clusters (Table ). These proteins were selected based on concordant ANOVA results between proteomics and transcriptomics data, and bibliographic analysis . Ten protein and RNA expression profiles were exactly the same between the three clusters (UGDH/ UGDH , K1C19/ KRT19 , FAS/ FASN , HYEP/ EPHX1 , BLVRB/ BLVRB , FSCN1/ FSCN1 , MOES/ MSN , FLNB/ FLNB , ACTN1/ ACTN1 , and SERPH/ SERPINH1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These biological characteristics provide evidence of biological aggressiveness of C2 tumors compared to C1 and C3. Interferon pathway, represented by STAT1, SYWC, AMPL, TYPH, and SAMH1, [24] K2C8 (KRT8) [24] K1C18 (KRT18) [24] K1C19 (KRT19) [24] Androgen-regulated genes ANXA4 (ANXA4), [25] BLVRB (BLVRB) [25,26] FAS (FASN) [24][25][26][27] HYEP (EPHX1) [25] IDHC (IDH1) [25] UGDH (UGDH) [28] C2 Basal-like ILF2 (ILF2) [29] LDHB (LDHB) [30] Invasion, ECM ACTN1 (ACTN1) [31] FINC (FN1) [32][33][34] FLNB (FLNB) [35] FSCN1 (FSCN1) [36] PLOD3 (PLOD3) [33,37] POSTN (POSTN) [32][33][34] SERPH (SERPINH1) [33,38] TAGL2 (TAGLN2) [39] TENA (TNC) [32,33,40] TPIS (TPI1) [41] C3 Basal-like MOES (MSN) [42] Interferon pathway AMPL (LAP3) [43][44][45] SAMH1 (SAMHD1) [46] STAT1 (STAT1) [47] SYWC (WARS) [48] TYPH (TYMP) [49] Immunoglobulins IGHM (IGHM) [50] IGKC (IGKC) [50] and immunoglobulins, represented by IGKC and IGHM, support ...…”
Section: One-way Anovamentioning
confidence: 99%
“…Also, we found that ACTN1 overexpression-induced HCC cell proliferation was largely abrogated by the inhibitors of the YAP-TEAD complex, indicating that ACTN1-induced HCC cell proliferation are dependent on the context of inhibition of Hippo signaling. Notably, ACTN1 is also involved in the focal adhesion kinase-Src complex formation [38], destabilization of E-cadherin-based adhesions [28], and luminogenesis [39]. Therefore, more works are needed to uncover whether these ACTN1-related activities are implicated in HCC development and progression.…”
Section: Discussionmentioning
confidence: 99%